CONCRETE POLICY IS REQUIRED FOR PHYSICAL THERAPY OR PHYSIOTHERAPY, EDUCATION PROFESSION AND PROFESSIONALS IN PAKISTAN - Piryani2, Rano Mal Piryani1 , Suneel Piryani2 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2022)
Physical therapy or Physiotherapy is considered worldwide an independent health care profession but in Pakistan it is still a dependent one, mostly depends upon the referral of patients from physician, surgeons and other medical doctors/consultants. Most of the medical health professionals refer the patient little bit late to physiotherapists. 1